Brixenbach research catchment: Quantification of runoff process proportions in a small Alpine catchment depending on soil moisture states and precipitation characteristics. Issue 6 (10th June 2021) - Meißl, Gertraud; Geitner, Clemens; Batliner, Andreas; Klebinder, Klaus; Kohl, Bernhard; Markart, Gerhard
Abstract: The Brixenbach valley is a small Alpine torrent catchment (9.2 km 2, 820–1950 m a.s.l., 47.45°, 12.26°) in Tyrol, Austria. Intensive hydrological research in the catchment since more than 12 years, including a hydrogeological survey, pedological and land use mapping, measurements of precipitation, runoff, soil moisture and infiltration as well as the conduction of rainfall simulations, has contributed to understand the hydrological response of the catchment, its subcatchments and specific sites. The paper presents a synthesis of the research in form of runoff process maps for different soil moisture states and precipitation characteristics, derived with the aid of a newly developed Soil‐hydrological model. These maps clearly visualize the differing runoff reaction of different subcatchments. The pasture dominated areas produce high surface flow rates during short precipitation events (1 h, 86 mm) with high rainfall intensity, whilst the forested areas often develop shallow subsurface flow. Dry preconditions lead to a slight reduction of surface flow, long rainfall events (24 h, 170 mm) to a dominance of deep subsurface flow and percolation. Abstract : For the Brixenbach catchment, maps of runoff processes for different soil moisture states and precipitation characteristics were developed by applying a new Soil‐hydrological model to 52 soil profiles. The maps (here surface runoff for saturated conditions, rainfall: duration 1 h, sum 86 mm) clearly show the differing reaction according to the site characteristics for different subcatchments: The pasture dominated areas produce high surface flow rates during such a short precipitation event with high rainfall intensity, whilst the forested areas then often develop shallow subsurface flow.